Caregiving [videorecording (DVD)] - Aduba, Uzo (PBS, 2025)
From Executive Producer Bradley Cooper, this is the story of a group of paid and unpaid caregivers navigating the ups and downs of this deeply challenging and immensely meaningful work. Intertwining intimate personal stories with the untold history of caregiving, the documentary reveals both the state and the stakes of care in America today. Malcoma Brown- Ekeogu devotes herself to her husband's care in the final stages of his illness, even when she feels alone in the journey. As the home health aide to Sherril Johnson, who has multiple sclerosis, Zulma Torres provides care with the same kindness that she would for a family member. Matt Cauli juggles care for his young son with care for his wife, Kanlaya, in the wake of a health crisis keeping the family together against the odds. Kim and Guillaume Olloz raise a disabled daughter in a world not built for people with disabilities in a home filled with love and care. Tracy Eacret experiences the laughter and the tears of a bittersweet season with her father as his end-of-life caregiver. And the Gutierrez family contends with a chronic illness that makes a caregiver out of their tender-hearted 14-year-old son.